2018
DOI: 10.30773/pi.2018.04.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Patients with Chronic Schizophrenia and Related Clinical Factors

Abstract: ObjectiveThis study aimed to investigate clinical factors contributing to the low physical activity (PA) of patients with chronic schizophrenia. MethodsPA was measured in 50 outpatients with chronic schizophrenia using the International Physical Activity Questionnaire Short Form (IPAQ-SF). Psychopathology, psychosocial functioning, and extrapyramidal symptoms were assessed using the 18 item-Brief Psychiatric Rating Scale (BPRS-18), Global Assessment of Functioning (GAF), and Drug-Induced Extrapyramidal Symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(46 reference statements)
0
13
0
1
Order By: Relevance
“…The use of antipsychotic drugs is also related to problems with increase in appetite, weight gain, obesity and associated metabolic syndromes such as hyperglycaemia or type II diabetes [ 12 , 13 , 14 ]. It is also believed that physical activity in these patients may be influenced by drug-induced extrapyramidal symptoms [ 15 ]. All this means that patients with schizophrenia present higher rates of comorbidities and a higher incidence of mortality compared to the general population [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of antipsychotic drugs is also related to problems with increase in appetite, weight gain, obesity and associated metabolic syndromes such as hyperglycaemia or type II diabetes [ 12 , 13 , 14 ]. It is also believed that physical activity in these patients may be influenced by drug-induced extrapyramidal symptoms [ 15 ]. All this means that patients with schizophrenia present higher rates of comorbidities and a higher incidence of mortality compared to the general population [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, inactive schizophrenic patients had significantly higher levels of affective, positive and negative symptoms and druginduced Parkinson's disease than those who were minimally physically active. This study also indicated that EPS was a major obstacle to physical activity in schizophrenia (Lee et al, 2018). Studies have shown that adults engage in a variety of gardening activities involving moderate to high levels of physical activity (Oh et al, 2018).…”
Section: Discussionmentioning
confidence: 52%
“…At the same time, they will also be required to do some physical gardening work, such as climbing steps, slopes, walking or moving, bending, lifting, and carrying on various surfaces. All of these activities are effective in improving limb function (Lee et al, 2018). Studies have found that these practices can also prevent injuries to muscles and bones and might afford pain relief (S€ oderback et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence for a negative association between antipsychotic-induced (e.g. haloperidol) extrapyramidal symptoms and low physical activity among patients with schizophrenia [54]. These results raise the question whether the frequent use of antipsychotics in the schizophrenia spectrum disorder group may account for the delayed effect of physical therapy.…”
Section: Discussion Of Resultsmentioning
confidence: 99%